Usage Of Gelatin-Virus Balls And Liquid Virus Filled Gelatin Capsules To Control Coral Reef Diseases: Model For Phage Therapy - Bhagwan N. Rekadwad; Chandrahasya N. Khobragade (European Scientific Journal, ESJ, 2016)
Coral reefs are very sensitive to environmental pollution. Coral reefs frequently get infected by various bacteria, fungi, marine algae and protozoa. The diseases include Bacterial Infections (BI), Fungal Infections (FI), Black Band Disease (BBD), Black Overgrowing Cyanophyta (BOC), Black Aggressive Band (BAB), Lethal Orange Disease (LOD), Skeleton Eroding Band (SED), PEYssonnelia (PEY), PNEophyllum (PNE) and White Syndromes (WS). Here in we have proposed a proposed model in which cold water soluble gelatin will be used to prepare Gelatin virus balls (GVB) and Liquid virus filled and sealed gelatin capsules (LVFSGC). GVB and LVFSGC will be prepared as per standard protocol in the form of paintballs and capsules. Above mentioned infecting agents of Coral reefs will be used as inoculum for production their production on the pilot scale. These produced infecting agents will be added with specific viruses of infecting agent (host-specific viruses). After the lysis of cell (naturally/artificially), lysate containg host-specific viruses will be used as infecting viruses to the Coral reef infecting agents. This lysate will be used for preparation of GVB and LVFSGC. These paintballs and capsules contain host-specific viruses can be made to release on a surface of sea water and dispersed on affected coral reefs zone naturally by Sea water current/waves. The dispersed viruses from GVB and LVFSGC will attach to their host. Ultimately, the diseasecausing agent may be killed and the coral reef infection will be removed from sea water without any harm to the environment. GVB and LVFSGC will be used for the release of viruses against disease-causing agents. The GVB and LVFSGC will systematically kill and save the coral reefs.